Understanding the links between agriculture and health: Livestock and health - Catelo, Maria Angeles O. (International Food Policy Research Institute, 2006)
Agriculture is the main source of livelihood of the majority of people affected by HIV and AIDS globally, and it is being progressively undermined by the disease. In Sub-Saharan Africa AIDS is affecting the rural landscape in ways that demand a rethinking of development policy and practice, and parts of South Asia may soon face a similar situation.... There is clearly tremendous scope for agricultural policy to become more HIV-responsive, both to further AIDS-related objectives and to help achieve agricultural objectives. Yet there are no magic bullets. Land-labor ratios and the relative degree of substitutability between household resources, among other factors, will determine the possible responses to HIV/AIDS. If policy becomes more HIV- responsive, it will stay relevant and effective. By mainstreaming HIV/AIDS into the policy process and carefully monitoring the results, policymakers will help build up evidence of what works in different contexts, enhance learning, and ultimately leave people better equipped to address the multiple threats of the pandemic.